Efektivitas Metode Kerja Kelompok Pada Pembelajaran Seni Budaya Plat Logam Khusus Sma Negeri 7 Wajo - Lisa Syari Sahrang; Jamilah; Nurwahidah (VisArt: Jurnal Seni Rupa dan Design, 2025)
This study aims to examine the effectiveness of the group work method in increasing students’ active participation in Cultural Arts learning, specifically on the metal plate material at SMAN 7 Wajo, as well as to identify the obstacles faced by students during the group work process. The background of this research is based on the phenomenon of students’ lack of active involvement in group work activities, where most students tend to be passive and rely on a few dominant members. This condition leads to unequal contributions within groups and has an impact on the low achievement of overall learning objectives. This study employs a qualitative descriptive approach, with data collection techniques including observation, interviews, and questionnaires. The results indicate that the group work method has the potential to enhance students’ active participation; however, its effectiveness is highly dependent on teachers’ mentoring strategies, the management of group dynamics, as well as individual motivation and responsibility within the group. The obstacles encountered include low learning motivation, a lack of awareness of the importance of cooperation, and unequal task distribution